2015
DOI: 10.2147/ceor.s86599
|View full text |Cite
|
Sign up to set email alerts
|

The financial burden of sickle cell disease on households in Ekiti, Southwest Nigeria

Abstract: BackgroundStudies on economic impact of sickle cell disease (SCD) are scanty despite its being common among children in developing countries who are mostly Africans.ObjectiveTo determine the financial burden of SCD on households in Ado Ekiti, Southwest Nigeria.MethodsA longitudinal and descriptive study of household expenditures on care of 111 children with SCD managed at the pediatric hematology unit of the Ekiti State University Teaching Hospital was conducted between January and December 2014.ResultsThere w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…First, a very large number of families in this region of the world live in extreme poverty [10]. Second is the very nature of sickle cell anemia, which is an impoverishing disease due to its recurrent complications [11]. The present study showed that for 93.6% of the subjects, the cost of medical care related to sickle cell anemia was unaffordable.…”
Section: Perceptions and Appreciation Of The Supply Of Health Servicementioning
confidence: 66%
“…First, a very large number of families in this region of the world live in extreme poverty [10]. Second is the very nature of sickle cell anemia, which is an impoverishing disease due to its recurrent complications [11]. The present study showed that for 93.6% of the subjects, the cost of medical care related to sickle cell anemia was unaffordable.…”
Section: Perceptions and Appreciation Of The Supply Of Health Servicementioning
confidence: 66%
“…Elements of the criteria that did not apply to a particular study were marked as not applicable. All the studies fulfilled most of the quality criteria except for five studies that did not provide a sample size justification and power description . Also, 13 of the studies did not measure key potential confounding variables measured nor adjust for them statistically …”
Section: Methodsmentioning
confidence: 99%
“…Financial risk protection for health care should, therefore, be a priority for Nigeria. Varying incidence of CHE from spending on specific health conditions in Nigeria has been documented including noncommunicable chronic diseases, sickle cell disease, tuberculosis, outpatient and inpatient services, drugs for human immunodeficiency virus (HIV), and malaria treatment . The objective of this review is to systematically review scientific data from studies conducted in Nigeria that provide information on incidence and factors associated with CHE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial impact is devastating, especially for rural households in SubSaharan Africa -where 60% of the population live -with very limited access to even routine health care 3,4 .…”
mentioning
confidence: 99%